2018
DOI: 10.1140/epjd/e2017-80322-4
|View full text |Cite
|
Sign up to set email alerts
|

Atomic fluorescence emitted from a corona discharge in helium above and below saturated vapour pressure

Abstract: Abstract.A new apparatus was constructed to investigate the visible and near infrared fluorescence spectroscopy of electronically excited helium over a wide range of pressures and temperatures, covering both the gaseous and liquid phases. To achieve sufficient throughput, increased sensitivity was established by employing a micro-discharge cell and a high performance lens system that allows for a large collection solid angle. With this set-up, several thousand spectra were recorded. The atomic 3s1 S → 2p 1 P a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…41–49 It builds strongly on previous work on electronically excited bulk liquid and the use of fluorescence spectroscopy for detection. 50–64 The topic of electronically excited helium clusters has also been addressed by theory. 65–72…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41–49 It builds strongly on previous work on electronically excited bulk liquid and the use of fluorescence spectroscopy for detection. 50–64 The topic of electronically excited helium clusters has also been addressed by theory. 65–72…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49] It builds strongly on previous work on electronically excited bulk liquid and the use of fluorescence spectroscopy for detection. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] The topic of electronically excited helium clusters has also been addressed by theory. [65][66][67][68][69][70][71][72] Previous studies of electronically excited 4 He clusters established the presence of perturbed atomic-like states related to the 2p 1 P ' 1s 1 S and dipole-forbidden 2s 1 S ' 1s 1 S transitions of helium atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Baturo et al [11] reported an experimental study on the predissociation of the Rg-I 2 (Rg = rare gas atom) van der Waals complexes in their ion-pair excited electronic state. Finally, details on a new apparatus to investigate the visible and near infrared fluorescence spectroscopy of electronically excited helium over a wide range of pressures and temperatures in gaseous and liquid phases have been presented by Shiltagh et al [12].…”
Section: Progress In Molecular Dynamicsmentioning
confidence: 99%